A novel hypoxia-induced miR-147a regulates cell proliferation through a positive feedback loop of stabilizing HIF-1α. Issue 8 (2nd August 2016) - Wang, Fan; Zhang, Haoxiang; Xu, Naihan; Huang, Nunu; Tian, Caiming; Ye, Anlin; Hu, Guangnan; He, Jie; Zhang, Yaou
ABSTRACT: Hypoxia is a general event in solid tumor growth. Therefore, induced cellular responses by hypoxia are important for tumorigenesis and tumor growth. MicroRNAs (miRNAs) have recently emerged as important regulators of hypoxia induced cellular responses. Here we report that miR-147a is a novel and crucial hypoxia induced miRNA. HIF-1α up-regulates the expression of miR-147a, and miR-147a in turn stabilizes and accumulates HIF-1α protein via directly targeting HIF-3α, a dominant negative regulator of HIF-1α. Subsequent studies in xenograft mouse model reveal that miR-147a is capable of inhibiting tumor growth. Collectively, these data demonstrate a positive feedback loop between HIF-1α, miR-147a and HIF-3α, which provide a new insight into the mechanism of miR-147a induced cell proliferation arrest under hypoxia.